What Administrators Do and How? A Study of Occupational Efficacy and Job Activity of Educational Administrators - Basu, Mudasir (JOURNAL OF INDIAN EDUCATION, 2012)
The quality and standard aspect of education requires effective educational administrators more than anything else. An administrator’s efficacy involves achieving worthwhile goals that support one’s vision and mission. Further it also depends on his cognizance and understanding of the process, and his ability to cope with the change. The study sought to investigate the Occupational Efficacy and Job Activity of Educational Administrators at Secondary Level of Education. The sample comprised of 250 Educational Administrators (119 Educational Administrators from High School Level and 120 Educational Administrators from Higher Secondary School Level). The data were collected by using Standardised Occupational Self-Efficacy Scale and Job Activity Analysis Scale (Self-constructed Scale). Percentage statistics, t-test and Karl Pearson’s Coefficient of Correlation were used to analyse the data. The overall results revealed that Effective Educational Administrators differ significantly from Ineffective Educational Administrators with respect to their cognizance of Job Activity. A significant positive correlation exists between Occupational Efficacy and Effective Educational Administrators’ cognizance of Job activity and low correlation exists between Occupational Efficacy and Ineffective Educational Administrators’ cognizance of Job Activity.